Exercise training‐induced adaptations associated with increases in skeletal muscle glycogen content. (7th January 2013) - Manabe, Yasuko; Gollisch, Katja S. C.; Holton, Laura; Kim, Young‐Bum; Brandauer, Josef; Fujii, Nobuharu L.; Hirshman, Michael F.; Goodyear, Laurie J.
<x xml:space="preserve">Abstract</x> Chronic exercise training results in numerous skeletal muscle adaptations, including increases in insulin sensitivity and glycogen content. To understand the mechanism leading to increased muscle glycogen, we studied the effects of exercise training on glycogen regulatory proteins in rat skeletal muscle. Female Sprague Dawley rats performed voluntary wheel running for 1, 4 or 7 weeks. After 7 weeks of training, insulin‐stimulated glucose uptake was increased in epitrochlearis muscle. As compared with sedentary control rats, muscle glycogen did not change after 1 week of training, but increased significantly after 4 and 7 weeks. The increases in muscle glycogen were accompanied by elevated glycogen synthase activity and protein expression. To assess the regulation of glycogen synthase, we examined its major activator, protein phosphatase 1 (PP1), and its major deactivator, glycogen synthase kinase (GSK)‐3. Consistent with glycogen synthase activity, PP1 activity was unchanged after 1 week of training but significantly increased after 4 and 7 weeks of training. Protein expression of RGL(GM), another regulatory PP1 subunit, significantly decreased after 4 and 7 weeks of training. Unlike PP1 activity, GSK‐3 phosphorylation did not follow the pattern of glycogen synthase activity. The ~ 40% decrease in GSK‐3α phosphorylation after 1 week of exercise training persisted until 7 weeks, and may function as a negative feedback mechanism in response to elevated glycogen. Our findings suggest that exercise training‐induced increases in muscle glycogen content could be regulated by multiple mechanisms, including enhanced insulin sensitivity, glycogen synthase expression, allosteric activation of glycogen synthase, and PP1 activity.